SOSIALISASI EDUKASI PENTINGNYA PENDIDIKAN TINGGI DAN BEASISWA BAGI PELAJAR NU DI KECAMATAN NGRAHO KABUPATEN BOJONEGORO - Annisa Nur Rakhmawati; Hendrik Richard; Liza Choirun Nisa; Shochib Adianto; Muhamad Solikhin; Ferdinant Pakage; Aridatuz Zahroh; Aria Dian Tri Wahyuni; Arinda Eka Lidiastuti; Zainul Muttaqin (Jurnal Padamu Negeri, 2026)
Higher education plays a vital role in improving the quality of human resources and expanding future opportunities for the younger generation. However, many students still lack an adequate understanding of the importance of pursuing further studies and accessing available scholarships. This community service activity aimed to enhance the understanding and motivation of Nahdlatul Ulama (NU) students in Ngraho District, Bojonegoro Regency, regarding the importance of higher education and the scholarship opportunities that can support their continued studies. The activity was implemented through an educational socialization method using lectures, discussions, and question-and-answer sessions involving 40 participants. The stages of the activity included preparation, implementation, and evaluation through pre-tests and post-tests to assess participants' responses and level of understanding of the material presented. The results showed that the participants engaged actively in the activity, with an average increase in understanding of [please insert percentage increase from pre-test to post-test], and most participants demonstrated enthusiasm during the question-and-answer session, particularly on topics related to the benefits of higher education, pathways to university admission, and scholarship information. This socialization activity proved effective in improving the understanding and motivation of NU students, making it a strategic step in fostering educational awareness and access to further studies in Ngraho District.